Children's Responses to the Addition of Indian Scad (Decapterus russelli) Fish Protein Concentrated and Flavor to Traditional Food - Antonius Kurniawan; Aef Permadi; Agus Heri Purnomo (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
Nutrition improvement efforts are by providing additional food in addition to food eaten daily with the aim of restoring nutrition and health for children aged 3-6 years. Additional food can be local or factory food. The purpose of this study was to determine the response of children to traditional food with a gapit cake with the addition of indian scad (decapterus russelli) protein concentrated and flavor with sensory value analysis. The data design and analysis used are completely randomized design, analysis data with Kruskall wallis method. Using sensory parameters applied through hedonic tests, the determination of the best formula was carried out involving 30 panelists of untrained 3-6 years old children from 3 regions in Blora District. Research result organoleptic test of fresh indian scad fish averaged 7.204-7.548 and floating fish protein concentrate produced 33% of the raw material weight of fresh fish. The results of chemical tests on the protein concentrate of indian scad fish are water content of 10.27%, ash content of 6.21%, fat content of 2.33%, protein content of 45.38%, carbohydrate content of 35.81%. The best organoleptic test result for the gapit cake formula is the addition of 10% concentration of indian scad fish FPC and 0.3% durian flavor which is preferred by children aged 3-6 years in Blora area with an average organoleptic odor value of 1.96, taste 1.97, colour 1.97, and texture 1.93 approach the like score 2. Nutrition-wise, the product has the composition of 7.29 % moisture, 0.85 % ash, 12.88 % protein, 5.36 % fat, and 35.81 % carbohydrate.